A comparative analysis of thermal comfort, energy consumption, pollutant emissions, and visual comfort in a school building utilizing electrochromic and thermochromic windows - Sina Lashgari; Mohammad Hossein Jahangir (Energy Strategy Reviews)
This study investigates a school building, a structure particularly sensitive to thermal and visual comfort, simulated across three cities in Iran, each characterized by distinct climatic conditions. For each scenario, the thermophysical properties of selected glazing types were modeled under controlled parameters, including transparent and tinted states. The analysis focused on critical performance metrics, including average indoor air temperature during both peak hot and cold periods (August 17th and January 3rd), annual energy consumption, carbon dioxide emissions, and natural daylight availability within a representative classroom. The results reveal that conventional glass outperformed smart glass in heating mode, consistently achieving indoor temperatures closer to the desired setpoint across all three cities. However, in cooling mode, transparent thermochromic windows exhibited superior performance, maintaining average indoor temperatures of approximately 28 °C in the hottest climate and 25 °C in the coldest climate during occupied hours. Compared to buildings equipped with conventional windows, the most substantial reduction in annual natural gas consumption was observed in Yazd, with a decrease of 47.8 %, while the greatest reduction in total annual energy consumption occurred in Tabriz, at 37.2 %. However, these energy savings were accompanied by a decline in thermal comfort, which remains a significant challenge in this study. The highest level of visual comfort during the midday hours was achieved with the thermochromic window in its colored state (approximately 300lux), considering the specific lighting requirements for educational use.